Polydnavirus gene provides accurate identification of species in the genus Hyposoter (Hymenoptera: Ichneumonidae). Issue 4 (19th February 2015) - Pook, Victoria G.; Chapman, Eric G.; Janzen, Daniel H.; Hallwachs, Winnie; Smith, M. Alex; Sharkey, Michael J.; Schonrogge, Karsten; Broad, Gavin
Abstract Accurate identification of species of parasitoid Hymenoptera often requires the analysis of multiple genetic and non‐genetic traits. Here, we investigate the potential for nuclear polydnavirus (PDV) gene loci to provide species‐level discrimination in the parasitoid wasp genus Hyposoter (Hymenoptera: Ichneumonidae). A region of one PDV gene, Cys‐d9.2, was sequenced from nine species of wasps and an additional two PDV genes, Cys‐d9.1 and Rep‐c18.2, were sequenced from multiple specimens of one species of wasp. A Bayesian phylogenetic analysis of the Cys‐d9.2 sequences resulted in accurate identification of species and no intraspecific variation was observed in this gene, Cys‐d9.1 or Rep‐c18.2. Further statistical analyses showed that Cys‐d9.2 has a high prevalence of non‐synonymous nucleotide substitutions. Our results support the use of Cys‐d9.2 as an additional genetic locus for species delimitation in Hyposoter, highlighting the value of PDV gene information to taxonomists studying the ichneumonid subfamily, Campopleginae.